Examining the Impact of Candlenut Fruit Extract Cream on Hair Growth in Male Wistar Rats (Rattus norvegicus) - Fitriani, Anche Pratiwi; Wijaya, Johana Fransiska; Lina, Juliana; Fibrini, Dewi (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Hair loss can affect mental health. Natural compound-based hair treatments like candlenut fruit are becoming more popular due to their low side effects and growing scientific research on hair loss. This study aims to prove the effectiveness of candlenut fruit extract cream on the hair growth of male Wistar strain rats (Rattus norvegicus). Research method Laboratory experiment, Principle 3R (Replacement, Reduction, and Refinement): Reducing Rattus norvegicus Wistar male strain samples The 20 male rats in this study will be divided into four groups. Hair growth is examined with 5%, 10%, and 15% candlenut fruit extract cream. Research data was analyzed using SPSS. The results of testing hair growth in rats with 5%, 10%, and 15% doses of candlenut fruit extract cream were normally distributed. The control group had a significant value of 0.928 > 0.05, treatment group 1 had a value of 0.579 > 0.05, treatment group 2 of 0.829 > 0.05, and treatment group 3 of 0.451 > 0.05. Candlenut fruit extract cream is effective for increasing hair growth in Rattus norvegicus. This study concludes that candlenut fruit extract cream can accelerate the development of hair follicles in Wistar strain male white rats. Due to the heated manufacturing process, candlenut extract is safe to use.